Erratum: KALLAL, ROBERT J. & LAPOLLA, JOHN S. (2012) Monograph of Nylanderia (Hymenoptera: Formicidae) of the World, Part II: Nylanderia in the Nearctic. Zootaxa, 3508, 1–64. - Kallal, Robert J.; Lapolla, John S. (Zootaxa, 2012)
(Erratum)